Adiponectin, type 2 diabetes and cardiovascular risk. (29th August 2020) - Lindberg, Søren; Jensen, Jan Skov; Bjerre, Mette; Pedersen, Sune H; Frystyk, Jan; Flyvbjerg, Allan; Galatius, Søren; Jeppesen, Jørgen; Mogelvang, Rasmus
Abstract: Background: Adiponectin is viewed as an insulin-sensitizing hormone with anti-inflammatory effects. In accordance, plasma adiponectin is decreased in metabolic disorders including type 2 diabetes mellitus (T2DM). However, in spite of the apparently beneficially effects, recent data from large prospective studies have consistently linked high adiponectin levels with increased cardiovascular (CV) disease and mortality, thus questioning the positive view on adiponectin. Accordingly, we investigated the relationship between adiponectin, incident T2DM and subsequently CV events. Methods: We prospectively followed 5349 randomly selected men and women from the community, without T2DM or CV disease. Plasma adiponectin was measured at study entry. Median follow-up time was 8.5 years (IQR 8.0–9.1 years). During follow up, 136 participants developed T2DM. Following their diagnosis, 36 of the 136 participants experienced a CV event (myocardial infarction, ischaemic stroke, or CV death). Results: Participants with increasing adiponectin had reduced risk of developing T2DM ( p < 0.001). After adjustment for confounding risk factors (including age, gender, body mass index, physical activity, alcohol consumption, blood glucose, HbA1c, blood pressure, lipids, high-sensitivity C-reactive protein, estimated glomerular filtration rate, and plasma N-terminal pro-brain natriuretic peptide, competing risk Cox-regression analysis identified adiponectin as an independent predictor of T2DM: hazard ratio (HR) for each doubling of adiponectin 0.55 (95% CI 0.41–0.74; p < 0.001). After development of T2DM, the risk of a CV event more than doubled. Increasing adiponectin (adjusted for the confounding risk factors mentioned) was associated with reduced risk of CV events: HR 0.34 (95% CI 0.16–0.72; p = 0.005) for each doubling in plasma adiponectin. Conclusions: In conclusion, increasing plasma adiponectin is associated with decreased risk of T2DM and subsequently reduced risk of CV events.